Community Empowerment Through Asset-Based Tourism Development: A Case Study Of Romokalisari Adventure Land, Surabaya - Fatin, Afifah Dina; Tamrin, M. Husni; Arieffiani, Deasy; Wahyudi, Agus (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to analyze the implementation of the Asset-Based Community Development (ABCD) approach in managing Romokalisari Adventure Land, a natural tourist destination operated by low-income communities (MBR) in Surabaya City. A qualitative method was employed, with data collected through interviews, observations, and documentation. The findings indicate that while the Asset-Based principle has been effectively applied through the empowerment of Paguyuban ALR in managing tickets and micro-business stalls, challenges such as workforce retention and income disparities between micro-business operators and attractions remain significant barriers. The application of the Internally Focused principle allows communities to manage their assets independently; however, economic inequalities and unresponsive ticket pricing policies negatively impact community welfare. Furthermore, the relationship between the Department of Food Security and Agriculture (DKPP) and Paguyuban ALR has not been optimal in strategic decision-making. The main findings suggest that the success of the ABCD approach heavily relies on enhanced communication, clear SOP formulation, and ongoing training support